STUDY KELAYAKAN KAWASAN KULINER MALAM JL. CIKAPUNDUNG BARAT SEBAGAI DESTINASI WISATA WARISAN BUDAYA DI KOTA BANDUNG - Riza Taufiq (Yayasan Akrab Pekanbaru, 2019)
The aim of this research is to identify the existing condition of the Jl. Cikapundung Barat of Bandung night culinary region, resistant factors in developing and the effort of developing the region in order to support the cultural heritage tourism development region Alun-alun-Braga. The Methodology used is descriptive qualitative to describe data of the phenomena derived at the locus of the research namely Bandung Cultural and Tourist Office and the Region of Night Culinary Jl. Cikapundung Barat of Bandung. Interactive and SWOT analysis are used to analysis collected data as consideration to determine development strategy. Data collections were derived by observation at the locus and interview with Bandung Cultural and Tourism Office, food seller, visitors and the local society of the region. The discussion of this research is focused on development strategy based on SWOT analysis of the Jl. Cikapundung night culinary region of Bandung and assessment of the Alun-alun-Braga Region. The result is to integrate the Jl. Cikapundung Barat of Bandung as apart of the cultural heritage tourism development region Alun-alun-Braga.